Magic IQ Pen / Nur Jannah Sallehudin, Nor Ain Mon@Nor … [et al.] - SALLEHUDIN, NUR JANNAH; MON@NOR, NOR AIN; ABDULLAH, FATIN NAJWA SHAFIKA; BADARUDDIN, NOOR NABIHAH; SALIN, MOHD SHARIN (2017)
Learning is a process that is critical to raise the level of thinking of each individual. Since school days we have been exposed to 3M skills of reading, writing and arithmetic, the learning process according to experts is started when at home, where the learning session begins when the age of the baby again. Therefore we would like to take the approach of the learning process that includes many aspects of starting at the age of baby. This is because when a baby's brain development is very positive and easy brain to receive various sciences. Therefore we have created a tool to help and attract children from the age of your baby's age.